Proceedings of the 2005 ACM Symposium on Document Engineering 2005
DOI: 10.1145/1096601.1096606
|View full text |Cite
|
Sign up to set email alerts
|

Towards XML version control of office documents

Abstract: Office applications such as OpenOffice and Microsoft Office are widely used to edit the majority of today's business documents: office documents. Usually, version control systems consider office documents as binary objects, thus severely hindering collaborative work. Since XML has become a de-facto standard for office applications, we focus on versioning office documents by structured XML version control approaches. This enables state-of-the-art version control for office documents.A basic prerequisite to XML … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
(29 reference statements)
1
15
0
Order By: Relevance
“…Even when they are comparable they often suffer from excessive runtime or enormously large edit scripts. Other comparative studies have found these shortcomings as well [27,15]. Both studies have also found that XyDiff [21] is the only serious contender.…”
Section: Index Structure Comparisonmentioning
confidence: 98%
“…Even when they are comparable they often suffer from excessive runtime or enormously large edit scripts. Other comparative studies have found these shortcomings as well [27,15]. Both studies have also found that XyDiff [21] is the only serious contender.…”
Section: Index Structure Comparisonmentioning
confidence: 98%
“…Rönnau et al analyzed requirements for version control of XML documents produced by word processors or spreadsheets in [14]. For a broader selection of algorithms and more in-depth information on the individual algorithms one can consult the survey from Peters [12] on change detection in XML trees or the survey by Bille [1] on solutions for the general tree edit distance problem.…”
Section: Related Workmentioning
confidence: 99%
“…From [23], where several XML diff approaches were analyzed, we decided to choose JXydiff [4] which is a Java tool for detecting changes in XML documents. We chose this for the following reasons: 1) It has the main features to get XML differences: can manage all kinds of XML nodes, can detect move and update operations and is based on tree oriented algorithms.…”
Section: Versioning Modulesmentioning
confidence: 99%